2020
DOI: 10.1155/2020/6615575
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Mutations of Primary and Metastatic Lung Adenocarcinoma in Chinese Patients

Abstract: Lung cancer is still the leading cause of cancer-related death worldwide. Of lung cancer, lung adenocarcinoma (LUAD) is the most common subtype. Most patients with LUAD would develop into metastasis, which limits the available treatment. Targeted therapy and immunotherapy provided options for those advanced patients. But they also broached up challenges to identify the appropriate patients. This study aims to reveal the landscapes of genomic mutations in primary and metastatic LUAD and their actionability. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
8
1
Order By: Relevance
“…The library construction and sequencing were performed in the Clinical Laboratory Improvement Amendments (CLIA)/CAP-compliant Molecular Diagnostics Service Laboratory of Shanghai OrigiMed Co., Ltd. Methods were similar to our previous work ( 10 , 11 ). Briefly, the formalin-fixed paraffin-embedded (FFPE) tissues were deparaffinized by heating in a 60°C oven for 1 h. As a control, white blood cells from the paired whole blood samples were separated by centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…The library construction and sequencing were performed in the Clinical Laboratory Improvement Amendments (CLIA)/CAP-compliant Molecular Diagnostics Service Laboratory of Shanghai OrigiMed Co., Ltd. Methods were similar to our previous work ( 10 , 11 ). Briefly, the formalin-fixed paraffin-embedded (FFPE) tissues were deparaffinized by heating in a 60°C oven for 1 h. As a control, white blood cells from the paired whole blood samples were separated by centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…It was indicated that subclonal driver heterogeneity is high between untreated metastases and primary tumors [ 115 ], while in treated metastases the proportion of pre-selected clonal drivers increased dramatically [ 76 , 117 ]. In particular, the treatment induced a significantly higher number of actionable mutations in genes encoding proteins involved in PI3K-AKT and HER/ErbB pathways [ 30 , 76 , 120 ]. As part of treatment pressure, the origin of primary and metastatic niches affects the selection of the clonal alteration repertoire in metastatic lesions [ 13 , 119 , 120 ].…”
Section: Clonality Of Metastasesmentioning
confidence: 99%
“…In particular, the treatment induced a significantly higher number of actionable mutations in genes encoding proteins involved in PI3K-AKT and HER/ErbB pathways [ 30 , 76 , 120 ]. As part of treatment pressure, the origin of primary and metastatic niches affects the selection of the clonal alteration repertoire in metastatic lesions [ 13 , 119 , 120 ]. A pan-cancer evolution study suggested that clonal dissemination exhibits organ specificity, and NSCLC shows a common spreading pattern to lymph nodes, liver, bones and brain; however, the mechanisms underlying colonization tropism remain unclear [ 22 , 81 , 115 , 116 , 121 ].…”
Section: Clonality Of Metastasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The library construction, sequencing, and mutation calling were performed by the Clinical Laboratory Improvement Amendments (CLIA)/College of American Pathologists (CAP)compliant Molecular Diagnostics Service Laboratory of Shanghai OrigiMed Co., Ltd. Briefly, library construction from the FFPE (Formalin-fixed, paraffin-embedded) tissues, sequencing, mapping, mutation calling, and annotation followed the previous studies (13,14). FFPE tissues were first sliced into 4µm sections.…”
Section: Dna Sequencing and Genomic Analysismentioning
confidence: 99%